Security management at the National Institute of Management : to outsource or insource? (A) - Ravichandran, N., (SAGE Knowledge. Cases., 2016)
The Dean, Ms. Swati Bhargava of Narmada Institute of Management (NIM), a reputed state funded higher educational institution suggested in April 2014 to the Administrative Officer (AO) Col. S R Rao, VSM (Retd) to conduct a comprehensive review of the security contracts (manpower agency) of NIM based on their experience with four different agencies in the last four years. She brought to the attention of the AO, a number of administrative and operational issues that were plaguing the manpower agency contract execution at NIM, and suggested to the AO to find an innovative and effective arrangement. The central issue in the case is to decide whether to insource or outsource security contract.